Factors for detection of gunshot residue on shooter's hands - Nordin, Farah Ad-Din (2020)
cases is the evidence to prove a person had fired a firearm, or somehow was connected with the firing activity. Gunshot residues (GSR), particularly on shooter’s hand, could provide significant aid in such investigation. Therefore, this study was aimed to investigate the detection of GSR particles recovered from the hands of shooter using two sampling methods, namely stubbing and swabbing, on the basis of the types of firearms and ammunitions, as well as the varying sampling areas. By considering lead, barium and antimony as the criterion to definitely confirm the presence of GSR, the experimental results revealed that greater number of GSR particles was shown in those samples collected upon firing using revolver with .38 SPL ammunition compared to semi-automatic pistol with 9 mm ammunition (p= 0.034). No statistical significant association was evident between the sampling areas and the number of GSR particles detected (p= 0.545 for semi-automatic pistol; p= 0.218 for revolver). All stub samples (n=12) demonstrated positive detection of GSR particles, but only one single characteristic GSR particle was detected on swab samples. Further examination on the collection efficiency of respective sampling methods demonstrated no significant association between the types of firearms and the number of GSR particles detected from respective cartridge cases (p= 0.568). The number of swabbing from spent cartridge case showed no significant difference (p= 0.561). However, the experimental results showed that the intensity of GSR did not associated with the number of shots. Analysis of the GSR recovered from six different ammunition types also demonstrated the variations in the GSR profiles. This study has successfully detected the presence of GSR particles, which could serve as supporting evidence to relate a suspect to a shooting case. However, swabbing has limited ability in recovering GSR samples from the hands of shooter firing a single shot. The method is useful whenever a stub is not available at the scene or to recover GSR particle from a place unreachable by a stub, to avoid the loss of trace particles. Additionally, the swab method was suitable to extract GSR particles to be analysed from the internal compartment of fired cartridges, which allow for the forensic profiling of various ammunition types.